A Switch to the Duodenal Switch - Aniceto Baltasar; Nieves Pérez; Rafael Bou; Marcelo Bengochea; Carlos Serra (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2019)
Background: Duodenal Switch (DS) is a procedure that combines a Sleeve-Forming Gastrectomy (SFG) plus a biliopancreatic diversion (BPD) for the treatment of morbid obesity (MO) with a higher weight loss and resolution of comorbidities Objectives: Report our experience with 950 consecutive DS operations performed from 1994 to 2016.  Setting: Mix of teaching and private institution in a county hospital of Spain. Methods: We report an observational, retrospective and longitudinal study of 950 consecutive morbidly obese patients treated by DS surgery.  Results: We performed 518 open and 432 laparoscopic DS. Operative mortality was 0.84% (1.38% in DS and 0.38% in LDS), 4.84% had leaks, two had hepatic failures (0.2%) and malnutrition was present in 3.1%. At 5 years, the percentage of BMI lost was 80%, and percentage of expected BMI loss was more than 100%. Conclusions: DS is the most aggressive bariatric surgery (BS) technique, but with the best long-term weight loss. We describe operative complications and long-term follow-up guidelines.